The irony of ability and disability in John 9:1–41 - Thomaskutty, Johnson (HTS teologiese studies, 2022)
The story of the man born blind is constructed within a grand irony of ability and disability. The Johannine narrator develops the characterisation of the man born blind as a progressive, seeing and missional personality, whereas all others in the story appear as people without proper understanding and vision and those with lower perspectives. Although the world conceived the man as a sinner, Jesus understands him as a means for divine glorification; though the Jews are widely considered able people in the socioreligious terms, Jesus considers them as sinful. The article argues that people can overcome their physical disabilities with the help of spiritual foresight and mental stability; people’s physical abilities are not guarantees for their wholistic stability. In that sense, John 9:1–41 can be considered a paradigmatic narrative which demonstrates the experiences of the disabled and marginal sections of the 1st-century CE context.Contribution: This article presents the irony of ability and disability within John 9:1–41 and suggests a new way forward in interpreting the fourth gospel by taking into consideration the existential struggles of people with disabilities. As a theological interpretation of the fourth gospel, this article fits well within the scope of HTS Theological Studies.